Rethinking Livestock Systems: Embracing Multifunctionality for a Sustainable Future - Spinelli, Madison (2024)
A news post about the conference titled, “Multifunctionality of Livestock Grazing Systems: A Lever to Envision Its Possible Futures”, held on 19 April 2024 in Montpellier, France.